Jual Beli Emas Secara Kredit Perspektif Hukum Ekonomi Islam - Hardiati, Neni; Latifah, Ida; F, Fitriani (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This study discusses the law of buying and selling gold on credit from the perspective of Islamic economics law. Gold has a special status in fiqh muamalah, especially because of its nature as a currency and commodity. In buying and selling transactions, certain conditions must be met, especially related to regulations or sharia principles regarding buying and selling related to usurious goods such as gold. Credit transactions, which allow payments to be made in installments or postponed, are controversial due to concerns about usury. This study will explore the views of scholars and Islamic financial institutions on this transaction, as well as recommendations for gold buying and selling practices in accordance with sharia principles. Buying and selling gold on credit is a contract for the transfer of assets such as gold from one person to another which is carried out through credit. This study aims to describe activities regarding buying and selling carried out through credit. This study uses a descriptive qualitative research type, through a study of various literature and criticizing the problems found in the field if the sale contract. Sales carried out on credit in the context of gold as currency. Furthermore, sales on the law of gold buying and selling should only be able to trade gold when the contract is in cash and the value is the same, but if the status of gold is a commodity, then buying and selling gold on credit is permissible.